2021
DOI: 10.47460/uct.v25i109.457
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre uso problemático de internet y calidad de sueño durante la pandemia de COVID-19

Abstract: Se analizó la relación entre el uso problemático de internet y la calidad de sueño. La metodología fue no experimental, transversal y correlacional. La muestra fue no probabilística por conveniencia. Participaron 118 estudiantes de pregrado y postgrado de universidades e institutos superiores de la ciudad de Quito en Ecuador. Los instrumentos fueron el Cuestionario de Experiencias Relacionadas con Internet (CERI) y el Cuestionario de Pittsburg de Calidad de Sueño (PSQI). Se evaluó la asociación entre las varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
3
0
1
Order By: Relevance
“…Result similar to that evidenced in Peru with a prevalence of 21.4% of IAD in university students [ 65 ]. However, it differs from what was reported in Mexico, showing that 62.7% had IAD the general population [ 66 ], similarly in Ecuador with a prevalence of 51.0%, having university students as a population [ 67 ]. The prevalence of IAD is due to the fact that, during the COVID-19 pandemic, the internet became an essential tool that has maintained remote communication between people through social networks, videoconferences and video games; increasing the number of daily hours on the internet, causing the excessive use of these resources to lead to IAD in adolescents [ 68 ].…”
Section: Discussionmentioning
confidence: 73%
“…Result similar to that evidenced in Peru with a prevalence of 21.4% of IAD in university students [ 65 ]. However, it differs from what was reported in Mexico, showing that 62.7% had IAD the general population [ 66 ], similarly in Ecuador with a prevalence of 51.0%, having university students as a population [ 67 ]. The prevalence of IAD is due to the fact that, during the COVID-19 pandemic, the internet became an essential tool that has maintained remote communication between people through social networks, videoconferences and video games; increasing the number of daily hours on the internet, causing the excessive use of these resources to lead to IAD in adolescents [ 68 ].…”
Section: Discussionmentioning
confidence: 73%
“…Al respecto autores como: Altena et al, 2020;Brooks et al, 2020;Bruni et al, 2015;Iñiguez et al, 2021;Jniene et al, 2019;Medina-Ortiz et al, 2022;Ron y Cuéllar-Flores, 2020;Sánchez., 2021 concluyen que: la perturbación en la rutina de vida, la inseguridad ante un panorama desolador para afrontar la pandemia y el desmedido y mal uso de los dispositivos electrónicos, se convirtieron en un catalizador de los trastornos relacionados con el sueño, repercutiendo en forma directa en el componente de responsabilidad personal con la tarea educativa que se estaba desarrollando desde casa.…”
Section: Introductionunclassified
“…The exposure to stressful conditions related to lockdown or fear of be infected had a high impact on the mental health of the residents. As mentioned, (Iñiguez Jiménez et al, 2021) there was a greater use of electronic devices and the relation was mainly done remotely. When there is a dependence on technology and the use of the Internet sources, it is possible to experience adverse behavioral symptoms such as anxiety, depression and alterations in the sleep pattern (Telles & Voos, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There are some research done in Ecuador about the adverse effects that pandemic of COVID-19 has generated, showing that stress derives in sleep problems such as insomnia and stay long hours gotten up at night (Ramírez et al, 2020). According to a study done by (Iñiguez Jiménez et al, 2021) done in Quito, in a sample of 118 college students, almost 85% evidenced sleep problems during the pandemic. The study presented by (Cruz Montesinos et al, 2021) showed that young people are the most affected population with major problems with sleeping compared with children.…”
Section: Introductionmentioning
confidence: 99%